Polyethylene-naphthalate (PEN) ferroelectrets: cellular structure, piezoelectricity and thermal stability - Fang, Peng; Qiu, Xunlin; Wirges, Werner; Gerhard, Reimund; Zirkel, Larissa (IEEE Transactions on Dielectrics and Electrical Insulation, 2010)
Cellular polyethylene-naphthalate (PEN) ferroelectrets are useful as soft and flexible electromechanical transducer materials. Improved cellular PEN foams are prepared by means of a + inflation + stretchingprocess and investigated with respect to their structure and their applications-relevant properties. It is found that most of the cellular voids have heights below 8 extgreekmm. The polymer walls do not allow sufficient gas exchange between the voids and the ambient atmosphere, when the cellular films are exposed to atmospheric pressures between a millibar and a few bars. As expected for ferroelectrets, a threshold voltage for charging is observed: A reasonable piezoelectric coefficient d_3_3 is only found when the charging voltage is higher than 4 kV. Furthermore, d_3_3 increases with charging voltage and reaches saturation at approximately 8 kV. Annealing after charging or charging at elevated temperatures may enhance the thermal stability of the PEN ferroelectrets. The d_3_3 of properly annealed samples is stable up to the respective annealing temperatures, but the annealing process reduces the piezoelectric activity of charged ferroelectret films to some extent. Samples charged at suitable elevated temperatures show much better thermal stability than those charged at room temperature, but the charging temperature should be limited to values below the material's glass-transition temperature Tg. Furthermore, the relevant elastic modulus c_3_3 of PEN ferroelectrets may decrease upon thermal treatment.
EAM Import::2019-03-08